PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE DAN KOMPENSASI KOMISARIS SERTA DIREKSI, TERHADAP MANAJEMEN PAJAK - Habibi Habibi; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
This study aims to examine the effect of corporate governance characteristics and board of commissioners compensation and also board of directors compensation on tax management. Corporate governance characteristics are measured by the size of board, proportion of independent board and application of corporate governance. Board of commissioners and board of directors compensations are measured using the total amount of compensation received in year divided by firm revenue. While tax management is measured using the effective tax rate. This study also tests several control variables namely firm size, profitability, and leverage.Data for this study are obtained from annual report of non-financial companies listed in Indonesia Exchange Stock (BEI) in 2008-2013. The sampling method used to draw the sample is purposive sampling. The criteria of companies allowed from listed companies in the ratings of CGPI. Final sample is 57 companies from 2008-2013. The hypothesis testing use linear regression analysis.The results show that application of corporate governance and leverage significantly affects the tax management. While size of board, proportion of independent board, compensation, firm size, and profitability did not significantly affect tax management.